Determining the peak spatial-average specific absorption rate (SAR) in the human body from wireless communications devices, 30 MHz to 6 GHz. Specific requirements for using the finite difference time domain (FDTD) method for SAR calculations of mobile phones Part 3, (21st October 2020) - British Standards Institution,
No abstract available